A 32-day long fieldwork in Antarctica improves heat tolerance during physical exercise - MARTINS, YGOR A.T.; PASSOS, RENATA L.F.; MARQUES, ALICE L.; GONÇALVES, DAWIT A.P.; MENDES, THIAGO T.; Nuñez Espinosa, Cristian Andrés; RODRIGUES, LUIZ O.C.; WANNER, SAMUEL P.; MORAES, MICHELE M.; ARANTES, ROSA M.E.; SOARES, DANUSA D. (My University, 2022)
Abstract We evaluated the influence of a 32-day camping in Antarctica on physical performance and exercise-induced thermoregulatory responses. In Brazil, before and after the Antarctic camping, the volunteers performed an incremental exercise at temperate conditions and, two days later, an exercise heat stress protocol (45-min running at 60% of maximum aerobic speed, at 31°C and 60% of relative humidity). In Antarctica, core temperature was assessed on a day of fieldwork, and average values higher than 38.5°C were reported. At pre- and post-Antarctica, physiological (whole-body and local sweat rate, number of active sweat glands, sweat gland output, core and skin temperatures) and perceptual (thermal comfort and sensation) variables were measured. The Antarctic camping improved the participants' performance and induced heat-related adaptations, as evidenced by sweat redistribution (lower in the chest but higher in grouped data from the forehead, forearm, and thigh) and reduced skin temperatures in the forehead and chest during the exercise heat stress protocol. Notwithstanding the acclimatization, the participants did not report differences of the thermal sensation and comfort. In conclusion, staying in an Antarctic camp for 32 days improved physical performance and elicited physiological adaptations to heat due to the physical exertion-induced hyperthermia in the field.
Keywords: acclimatization; cold; performance; polar medicine; sweating; temperature